The long-term memory benefits of a daytime nap compared with cramming - Look, Carol (2019)
Study Objectives: Daytime naps benefit long-term memory relative to taking a break and remaining awake. However, the use of naps as a practical way to improve learning has not been examined, in particular, how memory following a nap compares with spending the equivalent amount of time cramming. Methods: Young adults learned detailed factual knowledge in sessions that flanked 1 hr spent napping (n = 27), taking a break (n = 27), or cramming that information (n = 30). Recall was examined 30 min and 1 week after learning. Results: When tested 30 min after learning, cramming and napping led to significantly better memory than taking a break. After a week, napping maintained this significant advantage, but cramming did not. Conclusions: These findings demonstrate the longer-term benefits of napping for retention of memoranda akin to what students encounter daily and encourage more widespread adoption of napping in education.